2021
DOI: 10.1051/0004-6361/202039415
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proton parallel temperature inside patches of switchbacks in the inner heliosphere

Abstract: Context. Switchbacks are discrete angular deflections in the solar wind magnetic field that have been observed throughout the heliosphere. Recent observations by Parker Solar Probe (PSP) have revealed the presence of patches of switchbacks on the scale of hours to days, separated by ‘quieter’ radial fields. Aims. We aim to further diagnose the origin of these patches using measurements of proton temperature anisotropy that can illuminate possible links to formation processes in the solar corona. Methods. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 59 publications
(20 reference statements)
1
43
1
Order By: Relevance
“…Surprisingly, Phan et al (2020) have reported that no reconnection signatures were observed inside the switchback transition regions, suggesting that switchbacks are isolated RD-type current sheets that do not undergo reconnection. On the other hand, Froment et al (2021) have recently provided direct evidence for magnetic reconnection occurring within the switchback transition regions, and (2) if magnetic reconnection does not commonly occur, what is the source (generation and/or evolution mechanisms) of the observed proton temperature increase (Woodham et al 2021) at the leading switchback transition regions? Recently, Woolley et al (2020) have shown that the parallel proton temperature does not vary across the switchback transition regions, further highlighting the role of local mechanisms in switchback evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Phan et al (2020) have reported that no reconnection signatures were observed inside the switchback transition regions, suggesting that switchbacks are isolated RD-type current sheets that do not undergo reconnection. On the other hand, Froment et al (2021) have recently provided direct evidence for magnetic reconnection occurring within the switchback transition regions, and (2) if magnetic reconnection does not commonly occur, what is the source (generation and/or evolution mechanisms) of the observed proton temperature increase (Woodham et al 2021) at the leading switchback transition regions? Recently, Woolley et al (2020) have shown that the parallel proton temperature does not vary across the switchback transition regions, further highlighting the role of local mechanisms in switchback evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The ion (proton) velocity, v i , and temperature, T i were primarily obtained from the SPAN-I (Livi et al 2020), but also the SPC (Case et al 2020), instruments of the SWEAP suite (Kasper et al 2016). The SPAN-I data consist of bi-Maxwellian fits to the proton core population, described in Woodham et al (2020), with the same selection criteria used for excluding bad fits from the dataset, and these data are used for v i and T i unless stated otherwise. Since the fluctuations investigated in this letter are at MHD scales, the solar wind velocity v is considered to be equal to v i .…”
Section: Datamentioning
confidence: 99%
“…Our main reason for using the data from four orbits of PSP, out of eight in total to date, is the availability of the SPAN-I data, which improve significantly after encounter 3. A Faraday cup instrument (SPC; Case et al 2019) also measures solar wind proton velocity on PSP but discrepancies between the two instruments exist (Woodham et al 2021). We choose to use data from SPAN-I, which provides more accurate data closer to the Sun, where the aberration allows the solar wind protons to fly into the instrument protected by the heat shield.…”
Section: Data Setmentioning
confidence: 99%